2020
DOI: 10.1016/j.joca.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nerves within osteochondral channels to osteoarthritis knee pain in humans and rats

Abstract: Contribution of nerves within osteochondral channels to osteoarthritis knee pain in humans and rats, Osteoarthritis and Cartilage,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 57 publications
(62 reference statements)
3
36
0
Order By: Relevance
“…Subchondral BMLs represent regions of subchondral bone characterized as displaying increased bone turnover, and expression of factors, including pro-inflammatory cytokines, that can increase nerve sensitization [ 5 ]. We previously showed that nerve growth factor expression within osteochondral channels, and subchondral osteoclast density, each is associated with knee OA pain [ 12 ], and calcitonin gene-related peptide immunoreactive sensory nerves within osteochondral channels are associated with pain in human and rat knee OA [ 15 ]. Activation of sensory nerves in subchondral bone might contribute to weight-bearing pain in knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Subchondral BMLs represent regions of subchondral bone characterized as displaying increased bone turnover, and expression of factors, including pro-inflammatory cytokines, that can increase nerve sensitization [ 5 ]. We previously showed that nerve growth factor expression within osteochondral channels, and subchondral osteoclast density, each is associated with knee OA pain [ 12 ], and calcitonin gene-related peptide immunoreactive sensory nerves within osteochondral channels are associated with pain in human and rat knee OA [ 15 ]. Activation of sensory nerves in subchondral bone might contribute to weight-bearing pain in knee OA.…”
Section: Discussionmentioning
confidence: 99%
“… 113 Calcitonin gene-related peptide-immunopositive (CGRP-IP) sensory nerve innervation has been shown to be significantly associated with OA pain manifestation, with the percentage of subchondral bone plate cavities containing CGRP-IP sensory nerves being obviously higher in the human symptomatic OA group than in the asymptomatic group. 114 …”
Section: Subchondral Bone Microenvironment In Oamentioning
confidence: 99%
“…Rather than cartilage, the abovementioned CGRP-IP nerve fibers in the osteochondral plate channels have been found to be more critical to OA pain in both humans and rats. 114
Fig. 5 Schematic diagram of OA pain.
…”
Section: Subchondral Bone Microenvironment and Oa Painmentioning
confidence: 99%
“…In general, systemic injection necessitates a 10 mg/kg dose, corresponding to 5 mg/injection [ 22 , 23 ]. Aso et al found that the inhibition of tropomyosin receptor kinase (TrkA), a high-affinity receptor of the NGF, reduced pain in meniscal transection-operated rats after oral treatment with 30 mg/kg twice daily [ 24 ]. Additionally, systemic administration of the NGF antibody in rat models increased limbs edema [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%